Using of telemedicine in treatment of severe community-acquired pneumonia in Krasnoyarsk state - N. V. Gordeeva; I. V. Demko; E. E. Korchagin; I. A. Soloveva; A. Yu. Kraposhina; M. G. Mamaeva; E. A. Verbitskaya (Медицинский совет, 2020)
Introducrion. Due to the peculiarities of the Krasnoyarsk krai (a huge territory, low population density, different levels of health development in the districts, personnel shortage), there is a need to increase the availability and quality of medical care to district patients. For this purpose, since 2016, the Regional telemedicine system has started functioning online monitoring for patients with severe pneumonia, which provides full-fledged curation of patients from all over the region.Objective. To evaluate the results of RTS monitoring of patients with severe pneumonia.Materials and methods. 770 cases of severe community-acquired pneumonia registered in RTS from 2016 to 2018 were analyzed. Statistical data processing was performed using variational statistics using the “Excel-7” software package. For all values, the minimum significance level (p) of 0.05 was taken into account.Results. The risk factor for severe flow was male. Among comorbid diseases, cardiovascular and bronchopulmonary diseases, diabetes, alcoholism and HIV infection prevailed. The lack of flu vaccination in 97% of patients increased the number of deaths by 4.5 times. The greatest need for consultation arose in the Central district hospitals of low capacity. The majority of patients are registered in the system on the first day of hospitalization and are consulted by a pulmonologist of the Regional clinical hospital within 2 hours. Air ambulance of the Regional clinical hospital evacuated 174 patients, the need for flights decreased by 3.5 times. The main mistakes of district hospitals in the management of patients were the irrational selection of antibacterial drugs, the volume of detoxification therapy, the late start of antiviral therapy and ventilators, and the lack of prescription of anticoagulants.Conclusions. Along with the presence of comorbidities, the outcome of the EAP is affected by the quality of medical care, which depends on the professional training of medical workers, continuity in the work of regional medical institutions and air ambulance, which causes difficulties, given the specifics of the region. RTS allows you to solve this problem at minimal cost.